Different Oral Appliance Designs Demonstrate Different Rates of Efficacy for the Treatment of Obstructive Sleep Apnea: A Review Article - Leonard A. Liptak; Edward Sall; Sung Kim; Erin Mosca; Shouresh Charkhandeh; John E. Remmers (Bioengineering)
Obstructive Sleep Apnea afflicts an estimated 1 billion people worldwide. Untreated, Obstructive Sleep Apnea is linked with elevated levels of mortality, decreased quality of life and increased economic costs. However, several large population studies demonstrate that the efficacy of Continuous Positive Airway Pressure therapy, the most frequently prescribed treatment for Obstructive Sleep Apnea, is compromised by frequent refusals and terminations. As a result, healthcare providers are evaluating non-CPAP treatment options. Oral Appliance Therapy has emerged as a leading non-CPAP treatment for patients with Obstructive Sleep Apnea. Historically, healthcare providers have questioned the efficacy of Oral Appliance Therapy. Dozens of Oral Appliances are available to healthcare providers, with many contemporary Oral Appliances featuring improved designs, materials and technologies. This review investigates whether Oral Appliance design matters; do different Oral Appliance designs demonstrate different rates of efficacy? To the best of the authors’ knowledge, this is the first review to exclusively focus on scientific papers that report treatment success with Oral Appliances as a residual Apnea Hypopnea Index of less than 10 events per hour. Out of 272 source papers, the 27 papers included in this review encompass a pooled sample of 3799 patients treated with six distinctly different categories of Oral Appliance designs. Chi-squared and two-sided Fisher’s exact tests indicate significant differences in efficacy amongst Oral Appliance designs. These findings suggest that certain Oral Appliance designs can enable highly efficacious treatment for patients with Obstructive Sleep Apnea. Given these findings, healthcare providers should consider design when selecting an oral device for patients diagnosed with Obstructive Sleep Apnea.